The effect of the Rostov corn bug population on the sown winter wheat varieties and the used insecticides - A. V. Kapustkina; V. A. Khilevsky (Зерновое хозяйство России, 2022)
Winter wheat occupies the main share in the structure of agricultural land in the Rostov region. The main factor in the deterioration of high-quality grain production in this area is the corn bug. Agrotechnical measures and plant protection products used in wheat cultivation have a significant impact on the formation, development and structure of the pest population. The purpose of the current study was to determine the effect of the sown winter wheat varieties on the number and phenotypic structure of the Rostov corn bug population under the use or absence of chemical treatments. In accordance with the “Methodical recommendations on the registration tests of insecticides, acaricides, molluscicides and rodenticides in agriculture” and phenogenetics methods, there have been conducted the analysis and registration of the corn bug number and the study of its phenotypic structure. There has been established that fluctuations in the number and changes in the intraspecific structure of the corn bug population depended on the varietal characteristics of the sown wheat. The most significant changes in the pest population were established on untreated sowings of the variety ‘Yuka’. There has been found out that the use of insecticides of different chemical classes reduces the number of bug larvae from 3 to 0 pcs./m2 , but at the same time, there is a transformation of the phenotype of the pest population, when the share of morphotype 1 in the structure increases on 13.5–23.5% and the share of morphotype 2 decreases on 10.4–36.3%. The greatest phenotypic modification of the corn bug population was registered on wheat sowings treated with insecticide Bi-58 New, EC (400 g/l), which indicates the need to limit its use or use in tank mixtures.